The representation of women in the government decision making in Hungary. Woman’s participation at the middle-level - Ványi, Éva (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2016)
The goal of this paper to examine women’s participation in Hungarian government decision making not only at ministerial level but also at state secretary level because political and bureaucratic state secretaries play important role in decision making process, too. The only place in the political decision making in Hungary where women can appear larger number is a deputy state secretary position. There are two reasons in the background: Hungarian political culture and political tradition and gate-keeper role of parties in recruitment process of powerful positions in cabinets. The paper covers the 1990–2014 period and shows changing of women’s participation at different governments and in varying government structure. The results are based on an empirical database which concludes data about top ministerial executive bodies. The database includes all political and bureaucratic leaders of governments from 1990 to June 2006 and from 2010 to June 2014.

Celem niniejszego artykułu było zbadanie udziału kobiet w podejmowaniu decyzji rządowych na Węgrzech. Zarówno na poziomie ministerialnym, jak i na poziomie sekretarzy stanu. Albowiem to właśnie sekretarze stanu na Węgrzech, na płaszczyźnie politycznej oraz biurokratycznej, odgrywają również istotną rolę w procesie podejmowania decyzji. Co więcej zaobserwowano, że jedynym miejscem, w procesie podejmowania decyzji politycznych na Węgrzech, gdzie może realnie pojawić się większa liczba kobiet są stanowiska zastępców sekretarzy stanu. Wynika to z zaistnienia dwóch głównych powodów: węgierskiej kultury politycznej i tradycji politycznej oraz funkcjonowania partii politycznych, jako swego rodzaju gate-keeperów, w procesie rekrutacji na najważniejsze stanowiska w gabinecie rządowym. Praca swym zasięgiem obejmuje lata 1990–2014, wskazując zmiany w zakresie udziału kobiet w różnych rządach oraz w ich strukturze wewnętrznej. Wyniki oparte są na badaniach empirycznych, które analizują kluczowe organy ministerialne oraz władzy wykonawczej. Analiza obejmuje wszystkich przywódców politycznych i administracje rządów od 1990 do czerwca 2006 r., a także od 2010 do czerwca 2014 r.
Udział kobiet w procesie podejmowaniu decyzji rządowych na Węgrzech
Keywords: women; participation; representation; government decision making; Hungary; kobiety; partycypacja; reprezentacja; proces podejmowania decyzji w rządzie; Węgry